“Técnicas de reforzamiento estructural en la rehabilitación de edificaciones patrimoniales” - Enma Luzmila, Delgado Caizaguano (2019)
Tangible heritage is all the material, movable and immovable property that have produced the different cultures of the country and that has a historical, artistic, scientific or symbolic significance for the identity of a community and the country. In the town, there are eleven private adobe buildings recognized as tangible heritage. For the most part, this type of construction has a stone foundation, adobe walls, mezzanine and wooden roof. Failures in walls caused by overtime, telluric movements, and their low tensile strength, indicate their bad seismic behavior, for this reason, the purpose of this research is to apply adequate reinforcement techniques that improve their seismic conditions, taking care of the compatibility of materials and preserving cultural authenticity, considering the level of intervention. For this, a failure was developed in walls and wooden elements, then a modeling for the initial state and another in which the reinforcement techniques are modeled, such as placement of a concrete plate on the mezzanine, the reinforcement of walls with electro-welded meshes and roof restoration. When modeling the building in both cases, the fundamental period was first determined, continuing with the control of torsion in the plant and checking of the efforts. Additionally, in the reinforced model, checks were carried out on the walls and in wooden sections. The reinforcement techniques applied improved the conditions of the building under a seismic analysis, thus protecting the life of the occupants.